2013
DOI: 10.1186/1746-6148-9-36
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerogenic risk assessment of diets for pigs in relation to gastric lesion prevalence

Abstract: BackgroundGastric ulcers in fattening pigs from intensive pork production can cause sudden deaths on farm and the grinding intensity of the diet appears to be among the risk factors. The objective of this work is to adopt the latest laboratory tests and thresholds for the ulcerogenic risk assessment of diets from experimental reports and verify the class of risk in relation to gastric lesion prevalence in reared finishers.ResultsSpecificity and accuracy of feed safety tests based on the ulcerogenic risk of fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…However, it is accepted that the grinding process will mainly affect the cereal component in the whole diet since the other ingredients already have small particle size. It is also possible that in the current study the particle size profile of the 'finely ground diets' were not 'fine' enough to result in stomach ulceration since Cappai et al (2013) defined a diet as 'high risk' when it contained more that 43% of particles under 0.4 mm. As noted above, the proportion of particles under 0.5 mm in the 'finely ground' diets in the current study was only 28% with 59% being between 0.5 and 1.4 mm.…”
Section: Feed Formmentioning
confidence: 72%
See 1 more Smart Citation
“…However, it is accepted that the grinding process will mainly affect the cereal component in the whole diet since the other ingredients already have small particle size. It is also possible that in the current study the particle size profile of the 'finely ground diets' were not 'fine' enough to result in stomach ulceration since Cappai et al (2013) defined a diet as 'high risk' when it contained more that 43% of particles under 0.4 mm. As noted above, the proportion of particles under 0.5 mm in the 'finely ground' diets in the current study was only 28% with 59% being between 0.5 and 1.4 mm.…”
Section: Feed Formmentioning
confidence: 72%
“…However, Wondra et al (1995) also reported that stomach lesions and keratinization increased with reduced particle size. Cappai et al (2013) recently classed feed containing 42.6% or more particles with a size o0.4 mm as 'high risk' of causing stomach ulceration since gastric lesions were found in 62% of finishing pigs offered such diets. On the other hand, Morel and Cottam (2007) found no significant difference in ADG or FCR when they compared barley particle sizes between 1000 and 434 mm and neither did I' Anson et al (2012) when comparing contrasting wheat particles.…”
Section: Introductionmentioning
confidence: 99%
“…However, considering the different result in the NEU to LYM ratio, further research on this issue is necessary. Cappai et al (2013) reported the involvement of blood leukocytes (mainly as LYM and NEU) in the local response to gastric mucosa 1 BHBA, D-3-Hydroxybutyrate; ALT, alanine aminotransferase; AST, aspartate aminotransferase; ALP, alkaline phosphatase; GGT, γ-glutamyltransferase; LDH, L-lactate dehydrogenase; TRAP, tartrate-resistant acid-phosphatase; CAB, plasma cation-anion balance.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of WECS in diets for growing and finishing pigs requires the assessment of possible effects on blood features that may result from diet-related stress due to the physical form or particle size of the feed, which can determine welfare problems like gastric ulcers (Cappai et al, 2013;Mason et al, 2013). At the same time, a possible reduction in mineral availability Blood parameters in fattening pigs fed whole-ear corn silage and housed in group pens or in metabolic cages 1 in the growing phase must be considered and monitored, namely because of changes in phosphorous availability compared to that of diets including wheat bran (Boyd et al, 1983;Gutzwiller et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is little data available to determine the best regimen for maximizing pig performance when feeding a limited amount of pelleted feed during the finishing period. From a health perspective, pelleting diets have been shown to increase the incidence of ulcers in finishing pigs, which can ultimately lead to increases in mortality (Friendship, 2004;Cappai et al, 2013). The effects of feeding pelleted feed for varying lengths of time or pulse feeding (switching between pelleted and meal diets) has been evaluated (Potter et al, 2010;, but its effects on stomach morphology are unknown.…”
mentioning
confidence: 99%